2015
DOI: 10.4103/0019-5154.159625
|View full text |Cite
|
Sign up to set email alerts
|

Role of depression, anxiety and stress in patients with oral lichen planus: A pilot study

Abstract: Context:Lichen planus is a psychosomatic disease. Higher frequency of psychiatric symptoms, poor quality of life, higher level of anxiety and neuroendocrine and immune dysregulations, all these factors, will enhance the exacerbation of the disease.Aims:The present study was to assess depression, anxiety and stress levels in patients with oral lichen planus.Materials and Methods:The psychometric evaluation using the Depression Anxiety Stress Scale (DASS)-42 questionnaire was carried out, by the same investigato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 9 publications
2
33
0
1
Order By: Relevance
“…Oral lichen planus patients showed higher than normal stress, anxiety and depression levels when evaluated by DASScale which was in accordance with by Shah B et al 3 , Kalkur C et al 16 , showed higher stress, anxiety and depression levels than normal evaluated by DASScale. Studies by Pekiner FN et al 17 , who stated that higher 21 also found higher anxiety and depression levels in OLP patients but using different psychometric tests which were in accordance with present study which proves strong association of OLP with stress, anxiety and depression levels.…”
Section: Discussion:-supporting
confidence: 79%
“…Oral lichen planus patients showed higher than normal stress, anxiety and depression levels when evaluated by DASScale which was in accordance with by Shah B et al 3 , Kalkur C et al 16 , showed higher stress, anxiety and depression levels than normal evaluated by DASScale. Studies by Pekiner FN et al 17 , who stated that higher 21 also found higher anxiety and depression levels in OLP patients but using different psychometric tests which were in accordance with present study which proves strong association of OLP with stress, anxiety and depression levels.…”
Section: Discussion:-supporting
confidence: 79%
“…Wilson's original description of LP already included the presence of hysteria, anxiety and depression as aetiological factors. Since then, many authors have demonstrated the importance of these psychological factors in the onset and development of the disease (Adamo et al, 2015;Alves et al, 2015;Čanković et al, 2015;Kalkur, Sattur, & Guttal, 2015;Sandhu et al, 2014;Suresh et al, 2015;Valter et al, 2013). Our results are similar to previous ones, considering that the HADS test showed higher levels of anxiety and depression among the OLP group patients than among the members of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety share the nonspecific factor of general distress. Stress is characterized by persistent tension, irritability, and a low threshold for becoming upset or frustrated (negative affect), and a tendency to overreact to stressful events (35). Any one of these three components can lead to psychological distress, thus any component can precipitate a dermatological or mucosal disorder, such as LP, or can lead to changes in levels of hormones associated with psychological distress, such as PRL (19).…”
Section: Discussionmentioning
confidence: 99%